2009
DOI: 10.4049/jimmunol.0802645
|View full text |Cite
|
Sign up to set email alerts
|

Role of TL1A in the Pathogenesis of Rheumatoid Arthritis

Abstract: TNF-like ligand 1A (TL1A), a member of the TNF superfamily, is the ligand of DR3 and DcR3. Several types of cells, such as endothelial cells, monocytes/macrophages, dendritic cells, and CD4 and CD8 T cells, are capable of producing this cytokine. In present study, we demonstrated that TL1A aggravated collagen-induced arthritis in mice. It increased collagen-induced arthritis penetrance and clinical scores as well as the severity of the pathological findings. TL1A administration led to the occurrence of multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
81
0
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 38 publications
7
81
0
6
Order By: Relevance
“…The presence of TL1A in diseased tissues, fluids, and sera from patients of chronic colitis and rheumatoid arthritis (RA) corroborates the findings in animal models (2,5,(17)(18)(19). In vivo studies of different animal models have provided direct evidence supporting the role of TL1A in autoimmune diseases.…”
supporting
confidence: 62%
See 2 more Smart Citations
“…The presence of TL1A in diseased tissues, fluids, and sera from patients of chronic colitis and rheumatoid arthritis (RA) corroborates the findings in animal models (2,5,(17)(18)(19). In vivo studies of different animal models have provided direct evidence supporting the role of TL1A in autoimmune diseases.…”
supporting
confidence: 62%
“…In vivo studies of different animal models have provided direct evidence supporting the role of TL1A in autoimmune diseases. We have demonstrated that the administration of recombinant TL1A to mice with collagen-induced arthritis (CIA) aggravates the disease (5). Furthermore, overexpression of TL1A in transgenic mice results in spontaneous inflammatory bowel disease as well as increased number of Th cells (9,20,21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…these results suggest a robust association of dcr3 with tl1a. a number of recent studies have illustrated the functions of TL1A in autoimmune diseases, including inflammatory bowel diseases (iBd) and ra (14,(31)(32)(33)(34)(35)(36). consistent with the role of tnf in inducing the release of tl1a, serum tl1a levels have been shown to substantially decrease in ra patients treated with adalimumab, an anti-tnf monoclonal ab (31), indicating that tl1a has a role in the progression rather than induction of the disease (36).…”
Section: Discussionmentioning
confidence: 92%
“…Purity of the naive CD4 ϩ cells was routinely greater than 95%. Purified naive T cells (0.25 ϫ 10 6 cells/well) were mixed with T cell-depleted irradiated (3000 rads) C57BL/6 feeder splenocytes (1.25 ϫ 10 6 cells/well) and cultured in 96-well plates under Th1, Th2, Th17, or Treg polarization conditions, as described in our earlier publication (31), and then analyzed by flow cytometry.…”
Section: Generation Of T Cell-specific Efnb1 and Efnb2mentioning
confidence: 99%